Revitalizing Local Culture Through the Gandrung Sewu Festival - Destiana, Amanda; Saputra, Diki Wahyu; Abdilah, Yoga Wisnu; Zaky, Aufa Muhammad; Wulandari, Saskia (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2025)
Cultural festivals are one of the effective strategies in maintaining the existence and revitalization of local culture amidst the challenges of globalization. This study focuses on the Gandrung Sewu Festival in Banyuwangi Regency, East Java, as a medium for preserving the traditional Gandrung dance art which is full of historical, religious, and social values. The purpose of this study is to describe how this festival is not only a mass art performance, but also a space for cultural dialogue involving the younger generation, local communities, government, and tourism actors. This study uses a qualitative approach based on literature review, referring to the historical research method from Gottschalk including heuristics, verification, interpretation, and historiography. Data sources were analyzed from various scientific articles, studies through interviews, and important documents that discuss the relationship between culture and tourism. The results of the study show that the Gandrung Sewu Festival has succeeded in revitalizing the meaning and role of the Gandrung dance as a symbol of local identity and as a tourist attraction that has a real economic impact on the community. The active involvement of the community in the festival forms a sense of belonging and strengthens sustainable cultural awareness. This festival also encourages the growth of the creative economy sector and strengthens Banyuwangi's image as a leading cultural destination. So Gandrung Sewu is not just an annual performance, but becomes a bridge connecting the past, present, and future of local culture. There, the community not only watches, but also participates in celebrating and preserving the cultural heritage that is their collective identity.